Forming of an innovative design of industry clusters as basis of preventive crisis regional management - G. S. MERZLIKINA (Real Economics Publishing House, 2017)
Significant institutional weaknesses of the formation of the management structure of an industry cluster are revealed, the possibility of engineering new structures of governance based on the principles of innovative management is identified. Feature of industrial clusters is the need and necessity of innovation that permeates all structures of the cluster management and all the processes of cluster management and, in turn, creates the preconditions for the formation of business entities the ability to successfully overcome a crisis situation. The purpose of the work is to develop the improved construction of innovational sectorial clustering with the use of effective centralized system of management of cluster business processes, based on diffusion of innovational technologies and their production embodiment. A typical structure of sectorial cluster management does not allow determining goals, tasks, tools, and mechanisms of innovational development of sectorial cluster’s enterprises. Drawbacks of the typical structure of sectorial cluster management are as follows: lack of representation of the scheme of cooperation between cluster members and external environment, format of development of interrelations between cluster’s elements in the sphere of information exchange, movement of material flows and financial resources, lack of formed areas of responsibility and matrices of competences of cluster members in various scenarios of development of external environment.The “structural imbalance” in the system of management of sectorial cluster is determined, which consists in elaboration of production and functional structure and “fuzziness” of responsibility for cluster activities efficiency. The use of the improved innovational construction of sectorial cluster management will eliminate structural imbalance in the process of management of sectorial clusters and increase effectiveness of their activities under the conditions of turbulent development of external environment.